IMPLEMENTATION OF SUSPECT RIGHTS IN THE CRIMINAL INVESTIGATION PROCESS - Fouza Azwir Abdul Aziz; Muzakkir (Jurnal Hukum Samudra Keadilan, 2024)
In the context of the occurrence of a criminal act, every law enforcer will adhere to the provisions of the Law of the Republic of Indonesia Number 8 of 1981 concerning the Criminal Procedure Code or commonly abbreviated as KUHAP which will be used as a guideline regarding the procedures for punishing a person suspected of committing a crime or so-called as a suspect. Basically the Criminal Procedure Code has clearly regulated matters relating to the rights of the suspect, the arrangements of which have been included in Articles 50 to 68 of the Criminal Procedure Code. As a positive law in Indonesia which is the basis for law enforcement, it has regulated the rights of suspects in the process of investigating criminal acts.